METHODOLOGY OF INCREASING QUALITY OF ELECTRICITY IN COMPANIES AND DISTRIBUTION ELECTRICAL NETWORKS - T. A. Ismailov; R. K. Gereykhanov; A. M. Magomedov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In this article methodologies of increasing quality of electricity are discussed. Analyses of different methodologies were made and new ways to compensate reactive power in companies were proposed.